Alienação e religião em Marx e Paul Tillich e a transição para um novo ser. - Silva, Edson Pereira da (2019)
The dissertation deals with Alienation and religion in Marx and Paul Tillich and the transition to a new Being. In general, it seeks to reflect in the authors' thoughts the relationship between alienation and religion, starting from Modernity and its apex with the transition to a new Being, according to the emerging paradigm of the sciences. In its specific form, at first, we will describe Karl Marx's concept of alienation and his critique of the religious, political and economic spheres. In his analysis, he concludes that the core of alienation is work according to the production model of the capitalist system and proposes communism as an answer. In the second moment, we will approach Paul Tillich. He states that the problem of alienation has not been overcome, as it is the result of an ontological separation of transcendent and immanent dimensions. In this way, alienation imposes an action that promotes reconciliation, reunion, creativity, meaning, and hope, which he calls the New Being, the Christ, as an answer to this question, in correlation with theology. In the third moment, we will point out that the alienation continues and that there are several indications that the rational, scientific knowledge model, of which Marx and Tillich are heirs, is in a deep and irreversible crisis. Given this, we will present, according to the emerging paradigm of science, a new Being, as a rupture and as the advent of a new era of human history, in which Modern Rationality has been overcome.